Implementasi Metode Simple Additive Weighting dan Machine Learning Untuk Rekomendasi Produk Skin Care Berbasis Android - Dana Pratiwi; Suroso Suroso; Jon Endri (STMIK Budi Darma, 2020)
Skin health, especially facial skin, is important because the face is the main attraction seen by others. This is closely related to the use of skincare products or skin care products that are used daily. Before determining which skincare product to use, it is very important to know the conditions and problems of facial skin. To make it easier to find out skin conditions and problems, researchers created an android-based application called